PENGARUH SIKAP KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN LABUHANBATU SELATAN - Sahrul Tarigan; Rasman .; Oryza Kuspranataga; T. Muhammad Iqbal; Puti Andam Sari (Manajemen dan Bisnis, 2021)
Problem of this study how influence of job attitude on performance. How influence of job environment on performance. How influence of  job motivation on  performance. How influence job attitude,  job environment and  job motivation on   performance. The purpose of this study to determine and analyze the effect of  job attitude on   performance. Determine and analyze the effect of   job environment on   performance. Determine and analyze the effect of  job motivation on   performance. Determine and analyze the effect of  job attitude,  job environment and  job motivation on   performance.  Sample in the study is 52 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job attitude variable has a positive and significant effect on performance.  Job environment variable has a positive and significant effect on   performance.  Job motivation variable has a positive and significant effect on performance. Job attitude,  job environment and  job motivation variable has a positive and significant effect on   performance.